Avaliação da viabilidade de incorporação de cinzas do bagaço da cana-de-açúcar em nanofibras poliméricas para uso como meios filtrantes - Sanson, Júlia Aparecida (Universidade Federal de São Carlos, 2025)
With the intensification of industrialization, the discharge of contaminants into the atmosphere increased, causing impacts on the environment. Furthermore, the high generation of agro-industrial waste has motivated the reuse of materials. In this sense, the development of technologies capable of treating polluted air and effluents becomes increasingly necessary, as well as the discovery of applications with greater added value for waste. Thus, the objective of this work was to evaluate the feasibility of incorporating sugar cane bagasse ash into polymeric nanofibers for use as filtering media for the treatment of contaminated air and water. The ash underwent grinding and sieving and the material was characterized to obtain particle size distribution, density, surface area and chemical composition. Cellulose acetate nanofibers were produced using the electrospinning technique. Ash was added to the polymeric solution, varying its mass from 185 to 1000 mg. The efficiency in collecting nanoparticles from the air was measured with an electric mobility particle analyzer and the pressure drop with a digital manometer. Adsorption tests were carried out with methylene blue solution in an experimental unit and the results were obtained using a UV/VIS spectrophotometer. The characterization of the ash indicated its adsorbent nature, given the high surface area, in the range of 51.40 to 95.40 m²/g, and the presence of silicon dioxide in 80.77%. Regarding incorporation, the addition of ash changed the structural and morphological characteristics of the nanofibers, causing a decrease in diameter. Among the filter media produced, those that showed the best performance were those with 6 hours of electrospinning, with emphasis on those with 185 and 500 mg of CBCA. Therefore, the results indicate that the incorporation of ash into nanofibers is promising.
Evaluation of the feasibility of incorporating sugarcane bagasse ash into polymeric nanofibers for use as filter media
Keywords: Cinzas do bagaço de cana-de-açúcar; Nanofibras; Electrospinning; Meios filtrantes; ENGENHARIAS::ENGENHARIA QUIMICA::OPERACOES INDUSTRIAIS E EQUIPAMENTOS PARA ENGENHARIA QUIMICA